PERAN HUBUNGAN MASYARAKAT DALAM MEWUJUDKAN TRANSPARANSI PEMERINTAHAN DAERAH - Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Nowadays, such organizations as government institusions are required to be more transparent in doing their operations or activities. Transparency refers to the availability of information to the public and clarity about government rules, regulations, and decisions. Corresponding to one of good governance principles, transparency in government decision making and public policy implementation reduces uncertainty. In building transparency, local government can utilize its public relations as an agent of communication to the citizens. Public relations has a strategic role in helping local government establish transparency in local government institutions. There is a shift in the role of public relations in such organization as government institution from the role as press agency, public,information, and two-way asymmetrical model to two-way symmetrical model of public relations.By implementing the two-way symmetrical model, public relations can help local government establish and maintain mutual relationship between government and its stakeholders.